Breast Reconstruction Using Pedicled Latissimus Dorsi Myocutaneous Flaps in Asian Patients With Small Breasts. (March 2017) - Chiang, I-Han; Wang, Chih-Hsin; Tzeng, Yuan-Sheng; Chiao, Hao-Yu; Chou, Chang-Yi; Wang, Chi-Yu; Chen, Tim-Mo; Chen, Shyi-Gen
Abstract : Background: The use of implants is still the most common procedure for breast reconstruction because they are easy, less painful than tissue transplants, and do not need a donor site. However, it is challenging to find a suitable implant for patients with small breasts, and some women fear foreign bodies and possible complications or reoperations. Autologous breast reconstruction using the pedicled latissimus dorsi (LD) myocutaneous flap without an implant provides a good option for Asian women with small breasts. Materials and Methods: Between June 1992 and December 2015, 31 patients underwent breast reconstruction with 33 LD flaps (29 unilateral and 2 bilateral). The skin paddle of the flap was designed with an oblique or transverse pattern depending on the mastectomy defect and the elasticity of skin. The thoracodorsal nerve was divided during flap harvesting to prevent a "twitching breast" postoperatively. Patients refused to have contralateral breast augmentation except for 2 with bilateral simultaneous augmentation after mastectomy bilaterally. Outcome measures were flap survival, shape and contour, symmetry of breast, complication of flap and donor site, patient satisfaction, and any local tumor recurrence or metastasis. Results: The mean patient age was 46.7 years (range, 27–72), and the mean body mass index was 22.5 kg/m 2 (range, 18.6–30). The mean size of the harvested skin paddle was 11.9 × 5.0 cm (range, 10 × 3 cm to 15 × 9 cm). Mean operative times were 200.8 minutes (range, 112–230 minutes) and 305 minutes (range, 300–310 minutes) for unilateral and bilateral reconstructions, respectively. Pathology reports showed a negative safety margin in all cases. Most cases were of invasive duct carcinoma (58%). All LD flaps survived, and the wounds healed satisfactorily over a mean follow-up of 49.9 months (range, 3–161 months). Donor sites were closed primarily with a hidden linear scar under the dorsal bra strap. Donor site morbidities were mainly seromas (15%), which were treated conservatively in most patients. Conclusions: The LD flap produced good autologous tissue for reconstruction, and no implants were needed for Asian women with small breasts. The reconstructed breasts showed good shape, contour, and symmetry. The results of donor site were acceptable and no significant functional loss. There were no major complications, and patient satisfaction was high.